Knowledge-sharing to enhance global health equity - Breagh Cheng; Salma Chaudhry; Brianna Cheng (McGill Journal of Medicine, 2022)
Knowledge produced by specialized professionals can be shared to promote public understanding and decision-making. During the COVID-19 pandemic, the application, translation, and dissemination of specialized knowledge has informed global policy responses and contributed to new vaccine technologies that protect against disease. However, the pandemic has also highlighted the potential impacts that ineffective knowledge dissemination and misinformation can have on health outcomes, which can further deepen health inequities between groups. Preliminary considerations are suggested for ways to foster a culture of knowledge sharing aimed at promoting global health equity.